2016
DOI: 10.1589/jpts.28.1496
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sitting posture on respiratory function while using a smartphone

Abstract: [Purpose] The purpose of this study was to investigate respiratory function in different sitting postures while using a smartphone. [Subjects and Methods] Fifty healthy volunteers were recruited. Participants were divided into 2 groups, a control group of participants who spent time as they liked for 1 hour, and a smartphone group of participants who spent time using a smartphone in a sitting position for 1 hour. To investigate changes in respiratory function, we measured forced vital capacity, forced expirato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 14 publications
0
13
2
Order By: Relevance
“…Furthermore, the PEF values in the present study were not found to have been significantly affected in either boys or girls who were addicted to smartphones. This finding is in line with the results of Kang et al ., who reported no significant changes in the PEF among adults who used smartphones frequently 14 . However, this finding did not support the results of Jung et al ., who reported that the PEF values in young adult smartphone users were significantly lower than among young adults who were not users 13 .…”
Section: Discussioncontrasting
confidence: 67%
See 3 more Smart Citations
“…Furthermore, the PEF values in the present study were not found to have been significantly affected in either boys or girls who were addicted to smartphones. This finding is in line with the results of Kang et al ., who reported no significant changes in the PEF among adults who used smartphones frequently 14 . However, this finding did not support the results of Jung et al ., who reported that the PEF values in young adult smartphone users were significantly lower than among young adults who were not users 13 .…”
Section: Discussioncontrasting
confidence: 67%
“…13 One study conducted by Kang et al reported that the kyphotic posture that developed among frequent smartphone users can alter lung function. 14 A slumped posture that occurs from poor habitual posture can negatively affect lung function as well. 12,15 Our study found gender differences with most of the PFT variables among boys being statistically significantly lower than those of girls.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…FHP is when the head moves anteriorly to the vertical line through the center of gravity (COG) [16,17] while the lower cervical spine is flexed and the upper cervical spine is hyperextended [18]. In addition to having FHP, smartphone users have also been found to have slumped posture [19]. It has been stated that FHP may impact the cervical spine as well as the thoracic spine and shoulder blades, which causing a general imbalance in the musculoskeletal system [10,13].De-la-Llave-Rincon et al (2009) [20] found that a reduced craniovertebral angle (CVA), which indicates larger FHP, might cause a reduction in the cervical range of mo-tion (ROM) [20].…”
Section: Introductionmentioning
confidence: 99%